Determinants of return intentions among internally displaced persons (IDPs) of Marawi City, Philippines. Issue 1 (2nd January 2020) - Collado, Zaldy C.
ABSTRACT: The article examines the determinants of return intentions among the Maranao internally displaced persons (IDPs), who had fled the war in Marawi City, Lanao Del Sur, Philippines. The study involved 10 key informant interviewees and 306 survey respondents. The results reveal that an overwhelming majority of the respondents wish to repatriate back home. Analysis shows that place attachment, good memories in relation to profit-making, and cultural identity contribute to the firm desire to return home. There is also a culturally appropriate response for their life recovery.